7.5k views
0 votes
Exercise is mixed —some require integration by parts, while others can be integrated by using techniques discussed in the chapter on Integration.

∫^2_1 (1-x^2)e^2x dx.

User Lenny D
by
5.1k points

1 Answer

3 votes

Answer:


-42.79587.

Explanation:

We have been given the indefinite integral
\int _1^2\:\left(1-x^2\right)e^(2x)\:dx. We are asked to find the integral using integration by parts.

We will use Integration by parts formula to solve our given problem.


\int\ vdv=uv-\int\ vdu

Let
u=1-x^2 and
v'=e^(2x).

Now, we need to find du and v using these values as shown below:


(du)/(dx)=(d)/(dx)(1-x^2)


(du)/(dx)=-2x


du=-2xdx


v'=e^(2x)


v=(1)/(2)e^(2x)

Upon substituting these values in integration by parts formula, we will get:


\int _1^2\:\left(1-x^2\right)e^(2x)\:dx=(1-x^2)((e^(2x))/(2))-\int _1^2((e^(2x))/(2))(-2x)dx


\int _1^2\:\left(1-x^2\right)e^(2x)\:dx=(1-x^2)((e^(2x))/(2))-\int _1^2 -xe^(2x)dx


\int _1^2\:\left(1-x^2\right)e^(2x)\:dx=(1-x^2)((e^(2x))/(2))+(1)/(4)(e^(2x)(2x)-e^(2x))

Let us compute the boundaries.


(1-2^2)((e^(2*2))/(2))+(1)/(4)(e^(2*2)(2*2)-e^(2*2))=-(3e^4)/(4)=-40.94861


(1-1^2)((e^(2*1))/(2))+(1)/(4)(e^(2*1)(2*1)-e^(2*1))=(e^2)/(4)=1.84726


-40.94861-1.84726=-42.79587

Therefore, the value pf the given definite integral would be
-42.79587.

User Yeralin
by
5.1k points